Midterm Outcomes of Surgical Repair of Partial Anomalous Pulmonary Venous Connection to SVC - Hu, Jie; Hu, Renjie; Zhang, Haibo; Zhang, Lei; Zhang, Wen; Chen, Dian; Dong, Wei (The Thoracic and Cardiovascular Surgeon, 2020)
Objectives We explore midterm results after surgical treatment of partial anomalous pulmonary venous connection (PAPVC) to superior vena cava (SVC) in our institution.Methods From 2008 to 2017, 78 patients underwent surgical repair for PAPVC to SVC. Patients were divided into three groups based on surgical techniques: Single-patch repair (n = 20, group A), double-patch repair (n = 31, group B), and Warden repair (n = 27, group C). Their median age was 1.9 years (range: 3 months–13.8 years); median weight was 11.4 kg (range: 4.4–39.7 kg). Clinical, electrocardiographic and echocardiographic were available for all patients.Results There were no early or late mortality. The mean follow-up duration was 1.8 ± 2.1 years (range: 0.6 months to 8 years). No pulmonary venous obstruction occurred and no residual left-to-right shunts sustained during the follow-up. Reoperation for SVC obstruction was required: 1 (5.3%) in group A, 1 (3.2%) in group B, and 2 (7.4%) in group C (p = 0.78). Four patients (3 in group B, 1 in group C, p = 0.7) presented transient rhythm disturbance at discharge and one patient in group B remains nonsinus rhythm during follow-up. Pacemaker was not required in all patients.Conclusion PAPVC to SVC can be safely managed by multiple techniques. Careful manipulation nearby sinus node must be emphasized during double-patch repair to prevent injury of sinus node. Obstruction of postoperative SVC stenosis should be paid attention to after Warden procedure. For young patients, operation should not be performed that early, but until preschool age.
Keywords: cardiac; pediatric; pulmonary arteries/veins; surgery; complications